Pengertian Teologis Gereja Berdasarkan Kitab-Kitab Taurat dan Implementasinya untuk Masa Kini - Agustinus Djali; Daya, Maswati (Sekolah Tinggi Teologi Borneo, 2024)
Abstract: Since the church was founded, it has been faced with problems. The fathers have triedto lay the foundation of church teachings very fundamentally, but until today it seems that theproblems have not disappeared, instead there are deviations in both doctrine and service thatopen up gaps for misguidance and cause church growth to stagnate. Therefore, the churchshould immediately introspect and return to its basic principles, namely